The Use of Pantyliners and Female Cleansing Soap Is Related to the Incident of Vucility in Teenage Women: Penggunaan Pantyliner Dan Sabun Pembersih Kewanitaan Berhubungan Dengan Kejadian Keputihan Pada Remaja Putri - Bella Dian Syah Fitri; Nispi Yulyana; Dwie Yunita Baska; Demsa Simbolon; Lela Hartini (Jurnal Kolaboratif Sains, 2026)
Vaginal discharge is the discharge of fluid other than blood from the vagina outside the normal range, whether it has an odor or not, and is accompanied by local itching. One of the problems that often occurs in adolescents in reproductive health is vagina dischaerge. The purpose of this study was to determine the factors associated with the occurrence of vaginal discharge in female adolescents at SMA Negeri 2 Bengkulu City. The study design used a cross sectional design. A sample of 103 female adolescents at SMA Negeri 2 Bengkulu City was taken using the Accidental Sampiling method. Showed that 75.7% of female adolescents experienced vaginal discharge and 24.3% did not experience vaginal discharge. Based on the results of statistical tests, there is a relationship between knowledge and the incidence of vaginal discharge p value (0.026) OR (5.750), there is a reletionship between personal hyginene and the incidence of vaginal discharge p value (0.034) OR (4.340), there is a reletionship between the use of pantyliners and the incidence of vaginal discharge p value (0.001) OR (5.786), there is a relationmship between the use of feminine hygiene soap and the incidence of vaginal discharge p value (0.014) OR (3.591), the most dominant factor is the use of pantyliners OR 5.277. There is a reletionship between pantyliners, the use of feminine hygiene soap and the incidence of vaginal discharge in SMA Negeri 2 Bengkulu City.